Iron depletion enhances the effect of sorafenib in hepatocarcinoma. Issue 6 (2nd June 2016) - Urano, Shinichi; Ohara, Toshiaki; Noma, Kazuhiro; Katsube, Ryoichi; Ninomiya, Takayuki; Tomono, Yasuko; Tazawa, Hiroshi; Kagawa, Shunsuke; Shirakawa, Yasuhiro; Kimura, Fumiaki; Nouso, Kazuhiro; Matsukawa, Akihiro; et al.
ABSTACT: Human hepatocellular carcinoma (HCC) is known to have a poor prognosis. Sorafenib, a molecular targeted drug, is most commonly used for HCC treatment. However, its effect on HCC is limited in clinical use and therefore new strategies regarding sorafenib treatment are required. Iron overload is known to be associated with progression of chronic hepatitis and increased risk of HCC. We previously reported that iron depletion inhibited cancer cell proliferation and conversely induced angiogenesis. Indeed iron depletion therapy including iron chelator needs to be combined with anti-angiogenic drug for its anti-cancer effect. Since sorafenib has an anti-angiogenic effect by its inhibitory targeting VEGFR, we hypothesized that sorafenib could complement the anti-cancer effect of iron depletion. We retrospectively analyzed the relationship between the efficacy of sorafenib and serum iron-related markers in clinical HCC patients. In clinical cases, overall survival was prolonged in total iron binding capacity (TIBC) high- and ferritin low-patients. This result suggested that the low iron-pooled patients, who could have a potential of more angiogenic properties in/around HCC tumors, could be adequate for sorafenib treatment. We determined the effect of sorafenib (Nexavar®) and/or deferasirox (EXJADE®) on cancer cell viability, and on cell signaling of human hepatocarcinoma HepG2 and HLE cells. Both iron depletion by deferasirox and sorafenib revealed insufficient cytotoxic effect by each monotherapy, however, on the basis of increased angiogenesis by iron depletion, the addition of deferasirox enhanced anti-proliferative effect of sorafenib. Deferasirox was confirmed to increase vascular endothelial growth factor (VEGF) secretion into cellular supernatants by ELISA analysis. In in vivo study sorafenib combined with deferasirox also enhanced sorafenib-induced apoptosis. These results suggested that sorafenib combined with deferasirox could be a novel combination chemotherapy for HCC.